ANALISIS PENGARUH PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Widaryanti Widaryanti; Nurul Latifah Pancawardani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
This study aims to determine the Accounting Control, Reporting System, and Clarity of the Targeted Budget for the Accountability of Government Institutions Performance. Methods of collecting data through a questionnaire given directly to the Head of Finance and Finance staff in all Regional Work Units (SKPD) in the City of Semarang. The test technique used is the validity test, reliability test, classic assumption test includes normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing in this study uses multiple linear regression analysis using Statistical Package for the Social Sciences (SPSS) 17 software. The results of empirical studies show that Partially Accounting Control has no effect on the Accountability of Government Agency Performance, Reporting Systems have a positive effect on Accountability of Government Agency Performance, and Clarity of Budget Targets have an effect on Accountability of Government Institutional Performance, While Simultaneously Accounting Control, Reporting System, and Clarity of Target The budget affects the Performance Accountability of Government Agencies